Special Issue: Technology in Applied Linguistics - Marina Dodigovic; Stephen Jeaco (Cranmore Publishing, 2022)
This issue endeavours to capture the plethora of such technologies in practice, using a variety of approaches which range from top-down institutional effort to bottom-up student-led grass-roots movements. The topics thus range from plagiarism detection to grammar, style and spell-checkers, including sub-topics such as Web-based learning, automated translation, social annotation tools, automated generation of language tasks, language corpora and concordancing. Accordingly, most of these themes are featured in the interview with Laurence Anthony, the creator of the well-known concordancer, AntConc (2019). This interview successfully encapsulates the sum total of applied linguistic encounters with technology, serving as the culmination of ideas presented in this issue.In the same vein, individual articles endeavour to explore at least some of the breadth and depth of the emerging technologies, as they are applied in teaching practice and the learning process. In the following we give a brief overview of the articles appearing in this issue.